Revitalization of Social Science and Pancasila and Civic Education Learning Materials on Information Technology-based in the City of Bekasi, West Java - Budiaman Budiaman; Rusmono Rusmono; Tjipto Sumadi (INOTEKS : Jurnal Inovasi Ilmu Pengetahuan, Teknologi, dan Seni, 2018)
This activity aims to revitalize information technology-based learning materials. The Social Science Teacher Association in the City of Bekasi frequently become the area to promote the information technology-based learning materials from publishers. The position of this Teacher Association seems merely as a distributor of learning material products. For this reason, empowerment of Social Science and Pancasila and Civic Education teachers is conducted in order to produce information technology-based learning materials. The implementation method of this activity begins with focus group discussions (FGD) between the chairman and the committee of  Social Science and Pancasila and Civic Education Teacher Association. The FGD’s results implemented in the form of mentoring program of  Social Science and Pancasila and Civic Education teachers with matter as follows:  (1) designing learning materials, (2) introduction to information technology, (3) create information technology-based learning materials, (4) create Edmodo online application and Appgeyser application, and (5) produce information technology-based learning materials.The outcome of the activities is in the form of information technology-based learning materials. The learning materials developed represent all Basic Competencies from 7th, 8th and 9th grades both in Social Sciences and Pancasila and Civic Education.